2014
DOI: 10.1111/ecog.00940
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between species richness and biomass changes from boreal to subtropical forests in China

Abstract: Diversity‐manipulation experiments suggest a positive effect of biodiversity on ecosystem properties (EPs), but variable relationships between species richness and EPs have been reported in natural communities. An explanation for this discrepancy is that observed richness–EPs relationships in natural communities change with environment and species functional identities. But how the relationships change along broad‐scale climatic gradients has rarely been examined. In this paper, we sampled 848 plots of 20 × 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 58 publications
18
82
0
Order By: Relevance
“…More specifically, it was found that species richness was significantly and positively correlated with AGC. Indeed, it is a well-known pattern, especially at the global scale, that carbon stocks increase with increasing diversity [27,29,65]. The positive relationships between tree species diversity and carbon stocks in this study supports the idea that diversity-carbon patterns are also identifiable even at smaller spatial scales.…”
Section: Agb and Agc Stocks At The Stand Levelsupporting
confidence: 83%
“…More specifically, it was found that species richness was significantly and positively correlated with AGC. Indeed, it is a well-known pattern, especially at the global scale, that carbon stocks increase with increasing diversity [27,29,65]. The positive relationships between tree species diversity and carbon stocks in this study supports the idea that diversity-carbon patterns are also identifiable even at smaller spatial scales.…”
Section: Agb and Agc Stocks At The Stand Levelsupporting
confidence: 83%
“…; He, Bertness & Altieri ; Prior & Bowman ), and evidence suggests that positive relationships between diversity and productivity are in fact more common where environmental conditions are most limiting (Paquette & Messier ; Wu et al . ; Toïgo et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…That could be related to the lower soil nutrient availability in conifer stands indicated by lower soil C:N ratio (Cools et al, 2014;Dawud et al, 2017), and thus to the need to allocate more biomass in fine roots in nutrient poor conditions (Finér et al, 2007;Helmisaari et al, 2007). In addition to diversity and identity effects other stand characteristics, soil properties and climatic conditions affect fine root productivity and these relationships have been studied in European forests (Finér et al, 2007;Helmisaari et al, 2007;Lehtonen et al, 2016) and other geographic areas (Finér et al, 2011;Wu et al, 2015). Fine root biomass has been shown to increase with stand basal area, age and soil C:N ratio in European forests (Finér et al, 2007;Helmisaari et al, 2007;Lehtonen et al, 2016), but the relationship between fine root biomass and mean annual temperature and precipitation has not been significant (Finér et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Reported relationships were positive (Schmid, 2002;Meinen et al, 2009a;Brassard et al, 2011, Brassard et al, 2013Laclau et al, 2013;Bu et al, 2017;Ma and Chen, 2017;Sun et al, 2017), insignificant (Hendricks and Bianchi, 1995;Schmid and Kazda, 2002;Bauhus et al, 2000;Meinen et al, 2009b, Meinen et al, 2009cJacob et al, 2010, Jacob et al, 2013Brassard et al, 2013;Lei et al, 2012b;Domisch et al, 2015;Ma and Chen, 2017) or negative (Bolte and Villanueva, 2006). The more numerous studies between tree species diversity and above-ground biomass and biomass production of trees show more consistent positive diversity effects (Zhang et al, 2012;Gamfeldt et al, 2013;Vilà et al, 2013;Ratcliffe et al, 2015;Toïgo et al, 2015;Wu et al, 2015;Jucker et al, 2016;Liang et al, 2016;Pretsch and Schütze, 2016), suggesting that tree species diversity effects on above-ground biomass or productivity are not necessarily mirrored by tree fine root productivity (Bauhus et al, 2000;Chen and Klinka, 2003;Brassard et al, 2011;Lei et al, 2012a). There are no comprehensive studies explaining the inconsistent responses of fine root biomass or productivity to tree species diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation